Review of Intricacies of Underwater Welding - Habibi Palippui (Collaborate, 2023)
One of the main challenges of underwater welding is the presence of water currents, which can make it difficult for the welder to maintain a stable position and affect the quality of the weld. Writing a literature review aims to identify gaps in existing knowledge and provide a theoretical framework for research. The research writing method involves identifying research questions, searching for relevant literature, evaluating the literature, organizing the literature, analyzing the literature, and synthesizing the literature. The research writing method involves identifying research questions, searching for relevant literature, evaluating the literature, organizing the literature, analyzing the literature, and synthesizing the literature. The research results should provide a theoretical framework, identify gaps, and provide recommendations for future research.